STRATEGY FORMULATION IN MANAGEMENT OF SUSTAINABLE ISLAMIC EDUCATIONAL INSTITUTIONS: STRATEGY FORMULATION IN MANAGEMENT OF SUSTAINABLE ISLAMIC EDUCATIONAL INSTITUTIONS - AHMAD JUNAIDI; Sulistyorini Sulistyorini; Agus Zaenul Fitri Agus Zaenul Fitri (As-Sulthan Journal of Education, 2026)
The success of Islamic Educational Institutions depends on leaders’ ability to formulate appropriate and accurate strategies. Through strategy formulation, Institutions can identify their strengths, weaknesses, opportunities, and threats. This study is library research with a qualitative approach. Primary data used is the book "Leadership Psychology and Management Psychology" Meanwhile, secondary data consists of books, articles, and other relevant sources. Data collection techniques were carried out by searching for sources, reading, reviewing, linking and recording necessary materials. Data analysis was carried out with reference to Miles and Huberman model, consisting of data condensation, data reduction, and drawing conclusions. This was refined by applying source triangulation to increase findings validity. The results of study indicate that strategy formulation is manifested in three activities: goal setting, environmental analysis, and aligning institution with environment. Fred R. David clarifies these three stages by establishing five strategy formulation phases: developing a clear vision and mission, analyzing external and internal environment, identifying strategic issues, selecting alternative strategies, and evaluating and selecting best strategy